2023
DOI: 10.3233/thc-220402
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of probiotics on the prevention of pouchitis for patients after ileal pouch-anal anastomosis: A meta-analysis

Abstract: BACKGROUND: To date, a few studies indicated that probiotics are beneficial to pouchitis, but no meta-analyses summarized the outcomes of probiotics in pouchitis in detail. OBJECTIVE: This meta-analysis discusses probiotics in the prevention of pouchitis for patients after ileal pouch-anal anastomosis (IPAA) and the relationship between probiotics preventive effect and the duration of therapy and history. METHODS: PubMed, EMBASE and Cochrane Library databases were searched from inception until February 2022. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Further studies focusing on the role of Lachnospiraceae in pouchitis pathogenesis are warranted. Moreover, several studies have shown the effectiveness of fecal microbiota transplantation (FMT) and probiotics in the treatment of pouchitis [34,35], which further highlights the role of microbes in the pathogenesis of pouchitis.…”
Section: Discussionmentioning
confidence: 99%
“…Further studies focusing on the role of Lachnospiraceae in pouchitis pathogenesis are warranted. Moreover, several studies have shown the effectiveness of fecal microbiota transplantation (FMT) and probiotics in the treatment of pouchitis [34,35], which further highlights the role of microbes in the pathogenesis of pouchitis.…”
Section: Discussionmentioning
confidence: 99%